The constitution of agency essays on practical reason and moral psychology - Korsgaard, Christine M. (Christine Marion) (Oxford : Oxford University Press, 2008)
Christine M. Korsgaard is one of the leading moral philosophers this volume collects ten influential papers by her on practical reason and moral psychology. She draws on the work of such great philosophers as Plato, Aristotle, Kant, and Hume, showing how their ideas can inform the solution of contemporary and traditional problems.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Practical reason; Ethics; Psychology and philosophy